Analisis Kemampuan Berbicara dalam Presentasi Ilmiah Mahasiswa Program Studi Pendidikan Teknologi Informasi STKIP Taman Siswa Bima - Ramdani Purnamasari (Medan Resource Center, 2022)
This research is a field research using a qualitative approach. This study aims to analyze students' speaking ability in scientific presentations in Indonesian language courses. The population of this study is 20 pepople students of the Information Technology Education Study Program who programmed Indonesian Language courses. Data collection techniques were carried out using tapping techniques in the form of video recordings. Based on the results of the study, students' speaking skills were obtained in aspects of pronunciation, grammar, vocabulary, fluency and understanding, including: on the aspect of pronunciation with the majority of respondents (8 respondents - 40%) with a weight of 3; Grammar aspect with the majority of respondents (10 respondents - 50%) with a weight of 3; Aspects of Vocabulary with the majority of respondents (11 Respondents - 55%); Smooth Aspect with the majority of respondents (9 Respondents - 45%); and the understanding aspect with the majority of respondents (9 Respondents - 45%) Based on the average achievement of the five aspects, the speaking ability of students of the Information Technology Education Study Program STKIP Taman Siswa Bima in scientific presentation activities is at a good level or category.